The development and initial validation of a questionnaire to measure help‐seeking behaviour in patients with new onset rheumatoid arthritis. (3rd June 2014) - Stack, Rebecca J.; Mallen, Christian D.; Deighton, Chris; Kiely, Patrick; Shaw, Karen L.; Booth, Alison; Kumar, Kanta; Thomas, Susan; Rowan, Ian; Horne, Rob; Nightingale, Peter; Herron‐Marx, Sandy; et al.
Abstract: Background: Early treatment for rheumatoid arthritis (RA) is vital. However, people often delay in seeking help at symptom onset. An assessment of the reasons behind patient delay is necessary to develop interventions to promote rapid consultation. Objective: Using a mixed methods design, we aimed to develop and test a questionnaire to assess the barriers to help seeking at RA onset. Design: Questionnaire items were extracted from previous qualitative studies. Fifteen people with a lived experience of arthritis participated in focus groups to enhance the questionnaire's face validity. The questionnaire was also reviewed by groups of multidisciplinary health‐care professionals. A test–retest survey of 41 patients with newly presenting RA or unclassified arthritis assessed the questionnaire items' intraclass correlations. Results: During focus groups, participants rephrased questions, added questions and deleted items not relevant to the questionnaire's aims. Participants organized items into themes: early symptom experience, initial reactions to symptoms, self‐management behaviours, causal beliefs, involvement of significant others, pre‐diagnosis knowledge about RA, direct barriers to seeking help and relationship with GP. The test–retest survey identified seven items (out of 79) with low intraclass correlations which were removed from the final questionnaire. Conclusion: The involvement of people with a lived experience of arthritis and multidisciplinary health‐care professionals in the preliminary validation of the DELAY (delays in evaluating arthritis early) questionnaire has enriched its development. Preliminary assessment established its reliability. The DELAY questionnaire provides a tool for researchers to evaluate individual, cultural and health service barriers to help‐seeking behaviour at RA onset.